2020
DOI: 10.3390/cancers12061430
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of POFUT1 Variants Associated with Colorectal Cancer

Abstract: Background: Protein O-fucosyltransferase 1 (POFUT1) overexpression, which is observed in many cancers such as colorectal cancer (CRC), leads to a NOTCH signaling dysregulation associated with the tumoral process. In rare CRC cases, with no POFUT1 overexpression, seven missense mutations were found in human POFUT1. Methods: Recombinant secreted forms of human WT POFUT1 and its seven mutated counterparts were produced and purified. Their O-fucosyltransferase activities were assayed in vitro using a chemo-enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…In CRC, POFUT1 silencing inhibited cell proliferation, decreased cell invasion and migration, arrested cell cycle progression, and stimulated CRC cell apoptosis in vitro and suppressed CRC tumor growth and transplantation in vivo [ 130 ]. Furthermore, structure and function studies on seven missense mutations in human POFUT1 in rare CRC cases showed that six of the missense mutations lead to an increase in the protein O -fucosyltransferase activity in vitro [ 131 ]. High levels of POFUT1 were found in glioblastoma (GBM) tissue, and GBM patients with high POFUT1 expression had a shorter survival rate.…”
Section: Significance Of Notch O -Glycosylation In...mentioning
confidence: 99%
“…In CRC, POFUT1 silencing inhibited cell proliferation, decreased cell invasion and migration, arrested cell cycle progression, and stimulated CRC cell apoptosis in vitro and suppressed CRC tumor growth and transplantation in vivo [ 130 ]. Furthermore, structure and function studies on seven missense mutations in human POFUT1 in rare CRC cases showed that six of the missense mutations lead to an increase in the protein O -fucosyltransferase activity in vitro [ 131 ]. High levels of POFUT1 were found in glioblastoma (GBM) tissue, and GBM patients with high POFUT1 expression had a shorter survival rate.…”
Section: Significance Of Notch O -Glycosylation In...mentioning
confidence: 99%
“…Thus, we first determined the propensity of recombinant mouse WIF1 EGF-LDs III and V purified from E.coli BL21 strain to be specifically in vitro modified with O -fucose by recombinant POFUT1 (recPOFUT1). As previously reported [ 11 , 37 , 56 ], O -fucosylation assays were followed either by click chemistry (CuAAC) and blotting technique or by trypsin digestion and mass spectrometry to specifically reveal and/or quantify EGF-LDs O -fucosylation ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may correlate with changes in the tumor microenvironment, such as inevitably diminished drug delivery caused by a reduction in tumor blood vessels. The differentially expressed proteins POFUT1 (24) and PKP2 (25) correlate with angiogenesis and fibrosis in other cancer species. Antiangiogenic therapy may be more effective for hyperdense PDAC patients than for hypodense PDAC patients.…”
Section: Discussionmentioning
confidence: 99%